Polycarbonate resin composition having excellent matting properties and solar reflectance

The polycarbonate resin composition, enhanced with copolymer resin, elastomer, and near-infrared reflecting pigment, addresses the challenge of achieving excellent mattness and solar reflectivity while preserving the mechanical properties of polycarbonate resin.

JP2025057900APending Publication Date: 2025-04-09SUMIKA POLYCARBONATE LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023167733
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing technologies fail to adequately combine good matting and solar reflectivity in polycarbonate resin compositions without compromising heat resistance and impact resistance.

Method used

A polycarbonate resin composition is developed by adding copolymer resin, elastomer, and near-infrared reflecting pigment to the polycarbonate resin, which achieves excellent mattness and solar reflectivity without sacrificing mechanical strength.

Benefits of technology

The composition produces molded products with enhanced matte appearance and solar reflectivity, maintaining the heat resistance and impact resistance of the polycarbonate resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025057900000001
    Figure 2025057900000001
  • Figure 2025057900000002
    Figure 2025057900000002
Patent Text Reader

Abstract

To provide a polycarbonate resin composition capable of producing a molded article having excellent matting properties and solar reflectance, without impairing inherent characteristics of polycarbonate resin such as heat resistance and impact resistance.SOLUTION: The present invention relates to a polycarbonate resin composition having excellent matting properties and solar reflectance. This composition comprises, relative to 100 pts.mass of a resin composition comprising 60 to 99.5 mass% of a polycarbonate resin (A) and 0.5 to 40 mass% of a copolymer resin (B), 0.1 to 20 pts.mass of an elastomer (C) and 0.1 to 20 pts.mass of a near-infrared reflective pigment (D).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polycarbonate resin composition having excellent matte properties and solar radiation reflectance. [Background technology]

[0002] Polycarbonate resin (PC) has excellent impact resistance, heat resistance, and transparency, and is widely used in various fields such as electrical / electronics, optics, building materials, medicine, food, and vehicles. On the other hand, when the surface is mirror-finished, the light transmittance is high, but the reflected light is strong in the direction of regular reflection from the light source, which can cause glare. For example, in outdoor building materials, the reflected light can be too dazzling, which can be a practical impediment.

[0003] In recent years, there has been an increasing demand for a matte appearance to give a sense of luxury in the fields of automobiles, furniture, and home appliances. In addition to design, for example, in automobile interior parts, if the surface of the molded product around the gauges is glossy, the reflected light may make it difficult to see the gauges, which may interfere with driving, so a matte appearance is also required from a safety perspective. Furthermore, when sunlight hits the in-vehicle equipment, the temperature rise may cause equipment failure, so in addition to a matte appearance, solar radiation reflection performance is also required.

[0004] As a method for obtaining a matte appearance, a method for forming unevenness on the surface using an embossing roll and a method for providing fine unevenness on the inner surface of an injection molding die have been proposed. However, when switching to molding of mirror-finished molded products, it is necessary to take measures in terms of facilities such as changing rolls and dies, which has the problem of reducing the overall production efficiency. A method for obtaining a matte appearance by applying paint is also known. However, there are problems such as the fact that dust and the like are easily attracted during painting, and the cost is high.

[0005] Patent Document 1 proposes a method of dispersing fine particles in a thermoplastic resin as a technique for modifying the resin itself. However, although a matte finish can be obtained, there is a problem in that the mechanical strength is reduced.

[0006] Patent Document 2 proposes a method of forming a surface layer of a material in which fine particles are dispersed in a resin, and molding this integrally with a substrate. However, this requires additional equipment, such as a multi-layer extrusion equipment for extrusion molding, or a two-color molding machine or two-color mold for injection molding, which increases costs.

[0007] Patent Documents 3 and 4 propose a method of thinly laminating fillers such as titanium oxide, mica, and aluminum oxide on the surface of a molded article in order to impart solar radiation reflection performance. However, since it is difficult to obtain good filler dispersion, the appearance of the molded article is sometimes impaired.

[0008] Patent Document 5 proposes a method of applying paint in which a pigment is dispersed in a solvent to the surface of a molded product. However, the need to use an organic solvent can place a burden on the environment.

[0009] Patent Document 6 proposes a method of performing secondary processing such as metal deposition or lamination of a metal layer on the surface of a molded product. However, since a special process is required for metal deposition, etc., this can lead to increased costs.

[0010] Thus, none of the conventional techniques described in Patent Documents 1 to 6 can fully satisfy the demand for a material having both good matte properties and solar radiation reflectivity. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Japanese Patent Application Laid-Open No. 63-137911 [Patent Document 2] Japanese Patent Application Publication No. 3-58840 [Patent Document 3] Japanese Patent Application Publication No. 11-13987 [Patent Document 4] Japanese Patent Application Publication No. 6-144874 [Patent Document 5] U.S. Patent No. 6,174,360 [Patent Document 6] JP 2010-64295 A Summary of the Invention [Problem to be solved by the invention]

[0012] An object of the present invention is to provide a polycarbonate resin composition capable of producing a molded article having excellent matte properties and solar radiation reflectance without impairing the inherent heat resistance, impact resistance, etc., of a polycarbonate resin. [Means for solving the problem]

[0013] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that by adding a copolymer resin, an elastomer, and a near-infrared reflective pigment to a polycarbonate resin, it is possible to obtain a polycarbonate resin composition which does not impair impact resistance, is inexpensive because no specific process is required, and can be used to produce a molded article which is excellent in both matte finish and solar radiation reflectivity, and which has been completed according to this finding.

[0014] That is, the present invention (1) is a polycarbonate resin composition having excellent matte properties and solar radiation reflectivity, characterized in that it contains 0.1 to 20 parts by mass of an elastomer (C) and 0.1 to 20 parts by mass of a near-infrared reflective pigment (D) per 100 parts by mass of a resin composition consisting of 60 to 99.5% by mass of a polycarbonate resin (A) and 0.5 to 40% by mass of a copolymer resin (B).

[0015] The present invention (2) relates to the polycarbonate resin composition having excellent matte properties and solar radiation reflectance according to the present invention (1), in which the copolymer resin (B) is a copolymer resin containing a structural unit derived from an olefin and a structural unit derived from a (meth)acrylic acid ester having an epoxy group.

[0016] The present invention (3) relates to the polycarbonate resin composition having excellent matte properties and solar reflectance properties according to the present invention (2), in which the copolymer resin (B) is an ethylene glycidyl (meth)acrylate copolymer, an ethylene glycidyl (meth)acrylate-vinyl acetate copolymer, or an ethylene glycidyl (meth)acrylate-methyl acrylate copolymer.

[0017] The present invention (4) is a polycarbonate resin composition having excellent matte properties and solar radiation reflectivity according to any one of the present inventions (1) to (3), in which the content of structural units derived from vinyl acetate is 4% by mass or less and the content of structural units derived from methyl acrylate is 28% by mass or less, based on 100% by mass of the copolymer resin (B).

[0018] The present invention (5) is the polycarbonate resin composition having excellent matte properties and solar radiation reflectance according to any one of the present inventions (1) to (4), in which the elastomer (C) is an acrylic core-shell elastomer.

[0019] The present invention (6) is the polycarbonate resin composition having excellent matte properties and solar reflectance properties according to any one of the present inventions (1) to (5), in which the elastomer (C) is a methyl methacrylate-butadiene-styrene copolymer or a methyl methacrylate-butadiene copolymer.

[0020] The present invention (7) relates to the polycarbonate resin composition having excellent matte properties and solar radiation reflectivity according to any one of the present inventions (1) to (6), wherein the near-infrared reflective pigment (D) is a composite oxide pigment containing two or more elements selected from chromium, iron, cobalt, titanium, antimony, aluminum, zinc, nickel, calcium and magnesium.

[0021] The present invention (8) is a molded article of the polycarbonate resin composition having excellent matte properties and solar reflectivity according to any one of the present inventions (1) to (7), which has a solar reflectance measured in accordance with JIS K5675-2011 of 12% or more and a gloss measured in accordance with JIS K5675-2011 of 50% or less. Effect of the Invention

[0022] According to the polycarbonate resin composition of the present invention, it is possible to obtain a molded article having a matte appearance and excellent solar radiation reflectance without impairing the heat resistance, impact resistance, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The polycarbonate resin composition of the present invention is characterized in that it contains 0.1 to 20 parts by mass of elastomer (C) and 0.1 to 20 parts by mass of near-infrared reflective pigment (D) per 100 parts by mass of a resin composition consisting of 60 to 99.5% by mass of polycarbonate resin (A) and 0.5 to 40% by mass of copolymer resin (B). By using the copolymer resin (B), elastomer (C), and near-infrared reflective pigment (D) in combination, it is possible to provide both a matte appearance and solar radiation reflectivity without impairing the inherent strength of the polycarbonate resin.

[0024] <(A) Polycarbonate resin> Polycarbonate resin (A) is a polymer obtained by the phosgene method in which various dihydroxydiaryl compounds are reacted with phosgene, or the transesterification method in which dihydroxydiaryl compounds are reacted with carbonates such as diphenyl carbonate. A representative example is a polycarbonate resin produced from 2,2-bis(4-hydroxyphenyl)propane (bisphenol A). Polycarbonate resin (A) is used alone or in a mixture of two or more types.

[0025] Examples of the dihydroxydiaryl compound include, in addition to bisphenol A, bis(hydroxyaryl)alkanes such as bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, bis(4-hydroxyphenyl)phenylmethane, 2,2-bis(4-hydroxyphenyl-3-methylphenyl)propane, 1,1-bis(4-hydroxy-3-tert-butylphenyl)propane, 2,2-bis(4-hydroxy-3-bromophenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, and 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane; Examples of the hydroxyaryl group include bis(hydroxyaryl)cycloalkanes such as 1,1-bis(4-hydroxyphenyl)cyclohexane, dihydroxydiaryl ethers such as 4,4'-dihydroxydiphenyl ether and 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, dihydroxydiaryl sulfides such as 4,4'-dihydroxydiphenyl sulfide, dihydroxydiaryl sulfoxides such as 4,4'-dihydroxydiphenyl sulfoxide and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, and dihydroxydiaryl sulfones such as 4,4'-dihydroxydiphenyl sulfone and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfone. These may be used alone or in combination of two or more. In addition to these, piperazine, dipiperidyl hydroquinone, resorcin, 4,4'-dihydroxydiphenyl, etc. may be used in combination.

[0026] Furthermore, the above dihydroxyaryl compounds may be used in combination with the following trivalent or higher phenol compounds. Examples of trivalent or higher phenols include phloroglucin (1,3,5-trihydroxybenzene), 4,6-dimethyl-2,4,6-tri-(4-hydroxyphenyl)-heptene, 2,4,6-dimethyl-2,4,6-tri-(4-hydroxyphenyl)-heptane, 1,3,5-tri-(4-hydroxyphenyl)-benzene, 1,1,1-tri-(4-hydroxyphenyl)-ethane, and 2,2-bis-[4,4-(4,4'-dihydroxydiphenyl)-cyclohexyl]-propane. These may be used alone or in combination of two or more.

[0027] The viscosity average molecular weight of the polycarbonate resin is usually 10,000 to 100,000, preferably 15,000 to 35,000, and more preferably 17,000 to 28,000. The viscosity average molecular weight can be adjusted by using a molecular weight regulator, a catalyst, etc., as necessary, when producing the polycarbonate resin. In this specification, the viscosity average molecular weight of the polycarbonate resin is measured by gel permeation chromatography (GPC).

[0028] <(B) Polymer resin> The copolymer resin (B) may be any known one that can impart matte properties to the polycarbonate resin (A) alone or together with other components, and may be selected from known copolymer resins. Examples of known copolymer resins include copolymer resins that contain structural units derived from olefins and structural units derived from (meth)acrylic esters having epoxy groups.

[0029] In this specification, the structural unit derived from an olefin means a structural unit formed by using an olefin as a monomer. The same applies to other structural units unless otherwise specified. In this specification, the structural unit derived from a (meth)acrylic acid ester having an epoxy group means a structural unit formed by using a (meth)acrylic acid ester having an epoxy group as a monomer. In this specification, the (meth)acrylic acid means one or both of acrylic acid and methacrylic acid, and the (meth)acrylate means one or both of acrylate and methacrylate.

[0030] Examples of olefins include ethylene, propylene, 1-butene, isobutylene, 2-butene, cyclobutene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-butene, 4-methyl-1-butene, cyclopentene, 1-hexene, cyclohexene, 1-octene, 1-decene, and 1-dodecene. These are used alone or in combination of two or more. Among these, ethylene is preferred.

[0031] Examples of (meth)acrylic acid esters having an epoxy group include glycidyl (meth)acrylate, epoxy (meth)acrylate, epoxycyclohexyl (meth)acrylate, and hydroxybutyl acrylate glycidyl ether. These may be used alone or in combination of two or more. Among these, glycidyl methacrylate is preferred.

[0032] The upper limit of the carbon number of the (meth)acrylic acid ester having an epoxy group is preferably 10 or less, more preferably 9 or less, and even more preferably 8 or less, and the lower limit is preferably 6 or more. Within these ranges, the function as a compatibilizer for the polycarbonate resin (A) and the elastomer (C) is more effectively exhibited, and a high compatibilizing effect tends to be obtained.

[0033] In 100% by mass of the copolymer resin (B), the lower limit of the content of the structural unit derived from an olefin is preferably 75% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more, and the upper limit is preferably 99% by mass or less, more preferably 97% by mass or less, even more preferably 93% by mass or less, and particularly preferably 90% by mass or less. Within these ranges, a high matte effect tends to be obtained.

[0034] In 100% by mass of the copolymer resin (B), the lower limit of the content of the structural unit derived from the (meth)acrylic acid ester having an epoxy group is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 7% by mass or more, and particularly preferably 10% by mass or more, and the upper limit is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less. Within these ranges, a high matte effect tends to be obtained.

[0035] The copolymer resin (B) may have a structural unit other than the structural unit derived from an olefin and the structural unit derived from a (meth)acrylic acid ester having an epoxy group. Examples of the structural unit include a structural unit derived from a (meth)acrylic acid ester having no epoxy group, and a structural unit derived from a vinyl compound such as vinyl acetate, acrylonitrile, or styrene. These may be used alone or in combination of two or more kinds.

[0036] In 100% by mass of the copolymer resin (B), the lower limit of the total content of the structural units derived from olefins and the structural units derived from (meth)acrylic acid esters having epoxy groups is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, and may be 100% by mass. Within the above range, a high matte effect tends to be obtained.

[0037] In 100% by mass of the copolymer resin (B), the upper limit of the content of the constituent unit derived from vinyl acetate is preferably 4% by mass or less, more preferably 2% by mass or less, even more preferably 1% by mass or less, and particularly preferably 0% by mass. Within the above range, a high matte effect tends to be obtained.

[0038] In 100% by mass of the copolymer resin (B), the upper limit of the content of the structural unit derived from methyl acrylate is preferably 28% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, particularly preferably 5% by mass or less, most preferably 2% by mass or less, even more preferably 1% by mass or less, and even more preferably 0% by mass. Within the above range, a high matte effect tends to be obtained.

[0039] In this specification, the content of each structural unit in the copolymer is a value measured by NMR.

[0040] Specific examples of the copolymer resin (B) include ethylene glycidyl (meth)acrylate copolymer, ethylene glycidyl (meth)acrylate-vinyl acetate copolymer, and ethylene glycidyl (meth)acrylate-methyl acrylate copolymer. Among them, ethylene glycidyl methacrylate copolymer is preferable. Specific products include Bondfast-E and Bondfast-2C, which are ethylene glycidyl (meth)acrylate copolymers manufactured by Sumitomo Chemical Co., Ltd., Bondfast-2B and Bondfast-7B, which are ethylene glycidyl (meth)acrylate-vinyl acetate copolymers manufactured by Sumitomo Chemical Co., Ltd., Bondfast-7L and Bondfast-7M, which are ethylene glycidyl (meth)acrylate-methyl acrylate copolymers manufactured by Sumitomo Chemical Co., Ltd., and Modiper A4400, which is an ethylene glycidyl (meth)acrylate-styrene-acrylonitrile copolymer manufactured by NOF Corporation.

[0041] The copolymer resin (B) may be a commercially available product, or may be synthesized by copolymerizing an olefin and a (meth)acrylic acid ester having an epoxy group. The polymerization method may be, for example, a known emulsion polymerization, suspension polymerization, solution polymerization, or bulk polymerization, or may be a combination of these polymerization methods.

[0042] The blending ratio of polycarbonate resin (A) and copolymer resin (B) is 60 to 99.5 parts by mass of polycarbonate resin (A) and 0.5 to 40 parts by mass of copolymer resin (B), preferably 80 to 99.5 parts by mass of polycarbonate resin (A) and 0.5 to 20 parts by mass of copolymer resin (B), and more preferably 92 to 98 parts by mass of polycarbonate resin (A) and 2 to 8 parts by mass of copolymer resin (B). If the blending ratio of copolymer resin (B) is less than 0.5 parts by mass, the matte effect is not sufficiently obtained, and if it exceeds 40 parts by mass, the appearance may be deteriorated.

[0043] <(C) Elastomer> The elastomer (C) is not particularly limited, but is preferably an acrylic elastomer, more preferably a polymer consisting essentially of an acrylic acid ester and / or a methacrylic acid ester, and further consisting of aromatic vinyl such as styrene, unsaturated hydrocarbon such as butadiene, and other copolymerizable monomers, if desired. The morphology is not limited, but it may be a core-shell type consisting of a continuous layer of hard segments and a dispersed layer of soft segments, or vice versa.

[0044] In the core-shell type, it is preferable to have a core layer formed from a rubber component and a shell layer formed by polymerizing a (meth)acrylic ester, and it is more preferable to have a core layer formed from a rubber component and a shell layer formed around the core layer by polymerizing a (meth)acrylic ester.

[0045] Examples of rubber components include polybutadiene-containing rubbers such as polybutadiene rubber and styrene butadiene rubber, silicone-based rubbers such as polyorganosiloxane rubber, polyisoprene rubber, polyalkyl acrylate-containing rubber, IPN-type composite rubbers consisting of polyorganosiloxane rubber and polyalkyl acrylate rubber, butyl rubber, and fluororubber. These are used alone or in a mixture of two or more. Among them, polybutadiene-containing rubbers are preferred, and polybutadiene rubber and styrene butadiene rubber are more preferred.

[0046] Examples of (meth)acrylic acid esters include (meth)acrylic acid esters of linear aliphatic alcohols such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and octyl (meth)acrylate, (meth)acrylic acid esters of cyclic aliphatic alcohols such as cyclohexyl (meth)acrylate, and (meth)acrylic acid esters of aromatic alcohols such as phenyl (meth)acrylate and benzyl (meth)acrylate. These may be used alone or in combination of two or more. Among these, methyl methacrylate is more preferable.

[0047] The upper limit of the number of carbon atoms in the (meth)acrylic acid ester is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less, and the upper limit is preferably 4 or more. Within these ranges, the effects tend to be more suitably obtained.

[0048] The shell layer is preferably formed by polymerizing aromatic vinyl together with (meth)acrylic acid ester. Examples of aromatic vinyl include styrene, α-methylstyrene, α-ethylstyrene, vinyltoluene, vinylnaphthalene, vinylanthracene, 3-methylstyrene, 4-methylstyrene, 4-isopropylstyrene, 2,4-dimethylstyrene, chlorostyrene, bromostyrene, 2,4-dichlorostyrene, 2-chloro-4-methylstyrene, and 2,6-dichloro-4-methylstyrene. These are used alone or in combination of two or more. Among them, styrene is preferred.

[0049] In 100% by mass of the elastomer (C), the lower limit of the content of the rubber component is preferably 8% by mass or more, more preferably 20% by mass or more, and even more preferably 40% by mass or more, and the upper limit is preferably 80% by mass or less, more preferably 60% by mass or less. Within these ranges, the effects tend to be more favorably obtained.

[0050] In 100% by mass of the elastomer (C), the lower limit of the content of the (meth)acrylic acid ester-derived component is preferably 5% by mass or more, more preferably 10% by mass or more, and the upper limit is preferably 92% by mass or less, more preferably 70% by mass or less, and even more preferably 50% by mass or less. Within these ranges, the effect tends to be more suitably obtained.

[0051] In this specification, the content of each component in the acrylic core-shell elastomer is a value measured by NMR.

[0052] Specific examples of the elastomer (C) include methyl methacrylate-butadiene-styrene copolymer (MBS), methyl methacrylate-acrylonitrile-butadiene-styrene copolymer (MABS), methyl methacrylate-butadiene copolymer (MB), methyl methacrylate-acrylic rubber copolymer (MA), methyl methacrylate-acrylic rubber-styrene copolymer (MAS), methyl methacrylate-acrylic-butadiene rubber copolymer, methyl methacrylate-acrylic-butadiene rubber-styrene copolymer, methyl methacrylate-(acrylic-silicone IPN rubber) copolymer, etc. These are used alone or in combination of two or more kinds. Among them, methyl methacrylate-butadiene-styrene copolymer (MBS) and methyl methacrylate-butadiene copolymer (MB) are preferred, and methyl methacrylate-butadiene-styrene copolymer (MBS) is more preferred.

[0053] Commercially available MBS (methyl methacrylate-butadiene-styrene copolymer) products include, for example, Paraloid EXL2603, Paraloid EXL2678, and Paraloid EXL2314 manufactured by Rohm and Haas Japan, E-870A and E-860A manufactured by Mitsubishi Chemical Corporation, and core-shell type graft copolymers such as Kane Ace M722 and Kane Ace M732 manufactured by Kaneka Corporation.

[0054] The elastomer (C) may be a commercially available product, or may be synthesized by polymerizing a (meth)acrylic acid ester, for example, by graft polymerization of a (meth)acrylic acid ester onto a rubber component. The polymerization method may be, for example, a known emulsion polymerization, suspension polymerization, solution polymerization, or bulk polymerization, or a combination of these polymerization methods.

[0055] The content of the elastomer (C) is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, and even more preferably 2 to 8 parts by mass, based on 100 parts by mass of the total of the polycarbonate resin (A) and the copolymer resin (B). If the amount added is less than 0.1 part by mass, the matte effect is not sufficiently obtained, and if it exceeds 20 parts by mass, the thermal stability and the appearance of the molded product are deteriorated.

[0056] <(D) Near infrared reflective pigment> The near infrared reflective pigment (D) is not particularly limited, but is preferably a composite oxide pigment containing two or more elements selected from chromium, iron, cobalt, titanium, antimony, aluminum, zinc, nickel, calcium, and magnesium. Examples of the composite oxide pigment include black pigments containing two or more elements selected from chromium, iron, cobalt, titanium, calcium, and magnesium, yellow pigments containing two or more elements selected from zinc, iron, titanium, antimony, and nickel, brown pigments containing two or more elements selected from titanium, antimony, chromium, iron, aluminum, and zinc, green pigments containing two or more elements selected from cobalt, nickel, zinc, and titanium, and blue pigments containing cobalt and aluminum.

[0057] Examples of black complex oxide pigments containing two or more elements selected from chromium, iron, and cobalt include compounds represented by the formula Cr2O3:Fe2O3:CoO, Cr2O3:Fe2O3, and (Co,Fe)(Fe,Cr)2O4. Specific examples of commercially available complex oxide pigments include 42-703A, 42-706A, 42-707A, 42-708A, and Black27 manufactured by Tokan Material Technology Co., Ltd., and Black3500 manufactured by Asahi Chemical Industry Co., Ltd.

[0058] An example of a black composite oxide pigment containing two or more elements selected from titanium, calcium, and magnesium is SG-101 manufactured by Ishihara Sangyo Kaisha, Ltd.

[0059] In addition, examples of yellow complex oxide pigments containing two or more elements selected from zinc, iron, titanium, antimony, and nickel include compounds represented by the formula (Zn,Fe)Fe2O4 and (Ti,Sb,Ni)O2. Specific examples of commercially available complex oxide pigments include Yellow 119 and Yellow 53 manufactured by Tokan Material Technology Co., Ltd., and Yellow 5150 manufactured by Asahi Chemical Industry Co., Ltd.

[0060] Furthermore, examples of brown complex oxide pigments containing two or more elements selected from titanium, antimony, chromium, iron, aluminum, and zinc include compounds represented by the formula (Ti, Sb, Cr)O2, Fe2TiO5:Al2O3, and (Zn, Fe)(Fe, Cr)2O4. Specific examples of commercially available complex oxide pigments include Brown 24, Brown 48, and Brown 33 manufactured by Tokan Material Technology Co., Ltd.

[0061] Examples of green composite oxide pigments containing two or more elements selected from cobalt, nickel, zinc, and titanium include (Co,Ni,Zn)2TiO4, etc. Specific examples of commercially available composite oxide pigments include Green50 manufactured by Tokan Material Technology Co., Ltd.

[0062] Examples of blue complex oxide pigments containing cobalt and aluminum include compounds represented by the formula CoAl2O4, etc. Specific examples of commercially available complex oxide pigments include Blue 28 manufactured by Tokan Material Technology Co., Ltd.

[0063] Among these composite oxide pigments, black composite oxide pigments containing two or more elements selected from chromium, iron, cobalt, titanium, calcium, and magnesium (for example, compounds expressed by the formula Cr2O3:Fe2O3:CoO, Cr2O3:Fe2O3, (Co,Fe)(Fe,Cr)2O4) such as 42-703A, 42-706A, 42-707A, and 42-708A manufactured by Tokan Material Technology Co., Ltd. and SG-101 manufactured by Ishihara Sangyo Kaisha, Ltd. are preferably used from the standpoint of design.

[0064] The content of the near-infrared reflective pigment (D) is 0.1 to 20 parts by mass, preferably 0.5 to 15 parts by mass, based on 100 parts by mass of the resin composition consisting of the polycarbonate resin and the copolymer resin (B). If the amount of the near-infrared reflective pigment (B) is less than 0.1 part by mass, the solar radiation reflectivity of the resulting resin molded product may not be sufficient, whereas if it exceeds 20 parts by mass, it leads to an increase in costs and is inferior in granulation properties, which is not preferable.

[0065] When the near-infrared reflective pigment (D) is mixed with the polycarbonate resin (A), a master batch containing a high concentration of the near-infrared reflective pigment (D) may be prepared and diluted for use. The vehicle (matrix resin) that is the base of this master batch may be a polycarbonate resin or another resin. Examples of other resins include polyester resins, polystyrene resins, and polyolefin resins.

[0066] The polycarbonate resin composition of the present invention may contain various known additives, polymers, fillers, etc., as necessary. For example, a hindered amine-based light resistance stabilizer may be added to suppress discoloration of a resin molded product when exposed to light for a long period of time, and a benzoxazole-based fluorescent brightener may be added to obtain a vivid color tone. Furthermore, these may be added in combination.

[0067] Examples of known additives include phenol-based or phosphorus-based heat stabilizers [2,6-di-t-butyl-4-methylphenol, 2-(1-methylcyclohexyl)-4,6-dimethylphenol, 4,4'-thiobis-(6-t-butyl-3-methylphenol), 2,2-methylenebis-(4-ethyl-6-t-methylphenol), n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-t-butylphenyl)phosphite, 4,4'-biphenylenediphosphinic acid tetrakis-(2,4-di-t-butylphenyl)phosphite, tetrakis ... t-butylphenyl), lubricants [paraffin wax, n-butyl stearate, synthetic beeswax, natural beeswax, glycerin monoester, montanic acid wax, polyethylene wax, pentaerythritol tetrastearate, etc.], colorants [titanium oxide, carbon black, dyes, for example], fillers [calcium carbonate, clay, silica, glass fiber, glass spheres, glass flakes, carbon fiber, talc, mica, wollastonite, various whiskers, etc.], flow improvers, spreading agents [epoxidized soybean oil, liquid paraffin, etc.] may be added as necessary.

[0068] The method for producing the polycarbonate resin composition of the present invention is not particularly limited. For example, A method in which polycarbonate resin (A), copolymer resin (B), elastomer (C), and near-infrared reflective pigment (D) are weighed and mixed together in a tumbler, ribbon blender, high-speed mixer, etc., and the mixture is then melt-kneaded and pelletized in a normal single-screw extruder or twin-screw extruder. A method in which some or all of the individual components are weighed separately and fed into an extruder from multiple feeders and melt-mixed; and a method in which the elastomer (C), near-infrared reflective pigment (D) and polycarbonate resin (A) and / or copolymer resin (B) are blended at high concentrations, melt-mixed, pelletized to form a master batch, and then the master batch is mixed with the polycarbonate resin (A) and / or copolymer resin (B) in a desired ratio. When these components are melt-mixed, any conditions such as the position at which they are fed into the extruder, the extrusion temperature, the screw rotation speed, the feed amount, etc. can be selected according to the situation, and the components can be pelletized.

[0069] There is no particular limitation on the method for producing a molded article from the polycarbonate resin composition. For example, the masterbatch and the polycarbonate resin (A) and / or copolymer resin (B) may be dry-mixed in a desired ratio, and then the mixture is directly charged into an injection molding apparatus or a sheet extruder apparatus to produce a molded article.

[0070] The molded article of the present invention is a molded article of the polycarbonate resin composition of the present invention having excellent matte properties and solar reflectivity, characterized in that the solar reflectance measured according to JIS K5675-2011 is 12% or more and the gloss measured according to JIS K5675-2011 is 50% or less. The solar reflectance is preferably 15% or more, more preferably 20% or more. The gloss value is preferably 40% or less, more preferably 30% or less.

[0071] In addition, the notched Charpy impact strength measured in accordance with ISO 179-2 is 10 kJ / m 2 More than 25 kJ / m is preferable. 2 The above is more preferable.

[0072] <Application> Molded articles obtained from the polycarbonate resin of the present invention can be suitably used as covers for on-board automobile parts which require a matte finish for design and safety reasons, and at the same time, solar radiation reflectivity. EXAMPLES

[0073] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "%" and "parts" are based on mass unless otherwise specified.

[0074] The raw materials used are as follows: (A) Polycarbonate resin Polycarbonate resin synthesized from bisphenol A and phosgene (SD Polyca 200-20, viscosity average molecular weight 18,800, manufactured by Sumika Polycarbonate Co., Ltd.) (B) Copolymer resin (ethylene glycidyl methacrylate copolymer) Bondfast E manufactured by Sumitomo Chemical Co., Ltd. (ethylene glycidyl methacrylate copolymer, content of structural units derived from ethylene: 88% by mass, content of structural units derived from glycidyl methacrylate: 12% by mass, content of structural units derived from vinyl acetate: 0% by mass, content of structural units derived from methyl acrylate: 0% by mass) (C) Elastomer (acrylic core-shell elastomer) EXL-2678 (methyl methacrylate-butadiene-styrene copolymer (core (rubber component): 50% polybutadiene by mass, shell: 50% styrene and methyl methacrylate) by mass) manufactured by Rohm and Haas Japan Co., Ltd. (D) Near infrared reflective pigment Tokan Material Technology Co., Ltd. 42-707A (composition: Cr2O3:Fe2O3)

[0075] Examples 1 to 7 and Comparative Examples 1 to 6 The ingredients were dry-wet mixed in a tumbler in the blending ratios shown in Tables 1 and 2, and then melt-kneaded at a melting temperature of 280°C using a twin-screw extruder (Shibaura Machine Co., Ltd., TEM37SS) to obtain pellets of the polycarbonate resin compositions of Examples 1 to 7 and Comparative Examples 1 to 6.

[0076] The solar reflectance, gloss, impact strength, and appearance of the resin compositions prepared in each of the Examples and Comparative Examples were evaluated by the following methods. The evaluation results are shown in Tables 1 and 2.

[0077] <Solar reflectance> The obtained resin composition pellets were dried at 120°C for 4 hours or more, and then a flat plate test piece (90mm x 150mm x 2mm thick) was prepared using an injection molding machine (ROBOSHOT S2000i100B manufactured by Fanuc Corporation) at a molding temperature of 300°C and a mold temperature of 80°C. Then, using a spectrophotometer (UH-4150 spectrophotometer manufactured by Hitachi High-Tech Science Corporation), the reflectance was measured at 1 nm intervals in the wavelength range of 300 to 2500 nm with a D65 light source, and the solar reflectance was calculated according to JIS K5675-2011 using the obtained reflectance value. During the measurement, the white plate was removed using a sample holder on the side of the integrating sphere to fix the test piece and perform the measurement. This solar reflectance value represents the solar reflectance of the sheet of the present invention, and the larger the value, the better the reflectivity in the near-infrared region. A solar reflectance of 12% or more was considered to be good.

[0078] <Gross> The obtained pellets of the resin composition were dried at 120°C for 4 hours or more, and then flat test pieces (80mm x 50mm x 2mm thick) were produced using an injection molding machine (ROBOSHOT S2000i100B manufactured by FANUC CORPORATION) at a molding temperature of 300°C and a mold temperature of 80°C. The obtained test pieces were used to measure the gloss at a measurement angle of 60° in accordance with JIS Z 8741. A gloss of 50% or less was considered to be acceptable.

[0079] <Impact strength> The resulting resin composition pellets were dried at 120°C for 4 hours or more, and then test pieces were prepared according to the ISO test method using an injection molding machine (FANUC CORPORATION, ROBOSHOT S2000i100B) at a molding temperature of 280°C and a mold temperature of 80°C. The notched Charpy impact strength of the obtained test pieces was measured according to ISO 179-2. The notched Charpy impact strength was 30 kJ / m 2 The above is considered a pass.

[0080] <Appearance> The appearance of the above molded article was visually inspected and evaluated according to the following criteria. ×: Defects in appearance such as delamination, silvering, jetting, and flow marks 〇: No appearance defects

[0081] [Table 1]

[0082] [Table 2]

[0083] From Table 1, when the polycarbonate resin composition satisfied the requirements of the present invention (Examples 1 to 7), all of them showed good results. On the other hand, as shown in Table 2, when the composition did not satisfy the requirements of the present invention (Comparative Examples 1 to 6), all of them had disadvantages.

[0084] In Comparative Example 1, since the ethylene glycidyl methacrylate copolymer (B) and the elastomer (C) were not added, the gloss was high and the matte property was poor.

[0085] In Comparative Example 2, the amount of the heat ray reflecting agent (D) was small, and therefore the solar reflectance was poor.

[0086] In Comparative Example 3, the blending amount of the ethylene glycidyl methacrylate copolymer (B) was small, and therefore the gloss was high and the matte property was poor.

[0087] In Comparative Example 4, the amount of the ethylene glycidyl methacrylate copolymer (B) blended was too large, and therefore the appearance of the molded article was poor.

[0088] In Comparative Example 5, the amount of elastomer (C) blended was small, so that the gloss was high and the matte properties were poor.

[0089] In Comparative Example 6, the amount of elastomer (C) blended was too large, and therefore the appearance of the molded article was poor.

Claims

1. A polycarbonate resin composition having excellent matte properties and solar radiation reflectivity, characterized in that it contains 0.1 to 20 parts by mass of an elastomer (C) and 0.1 to 20 parts by mass of a near-infrared reflective pigment (D) relative to 100 parts by mass of a resin composition consisting of 60 to 99.5% by mass of a polycarbonate resin (A) and 0.5 to 40% by mass of a copolymer resin (B).

2. 2. The polycarbonate resin composition according to claim 1, wherein the copolymer resin (B) is a copolymer resin containing a structural unit derived from an olefin and a structural unit derived from a (meth)acrylic acid ester having an epoxy group.

3. 3. The polycarbonate resin composition according to claim 2, wherein the copolymer resin (B) is an ethylene glycidyl (meth)acrylate copolymer, an ethylene glycidyl (meth)acrylate-vinyl acetate copolymer, or an ethylene glycidyl (meth)acrylate-methyl acrylate copolymer.

4. 2. The polycarbonate resin composition according to claim 1, wherein, based on 100 mass% of the copolymer resin (B), the content of structural units derived from vinyl acetate is 4 mass% or less and the content of structural units derived from methyl acrylate is 28 mass% or less.

5. 2. The polycarbonate resin composition having excellent matte properties and solar radiation reflectance according to claim 1, wherein the elastomer (C) is an acrylic core-shell elastomer.

6. 6. The polycarbonate resin composition according to claim 5, wherein the elastomer (C) is a methyl methacrylate-butadiene-styrene copolymer or a methyl methacrylate-butadiene copolymer.

7. 2. The polycarbonate resin composition according to claim 1, wherein the near-infrared reflective pigment (D) is a composite oxide pigment containing two or more elements selected from the group consisting of chromium, iron, cobalt, titanium, antimony, aluminum, zinc, nickel, calcium and magnesium.

8. A molded article of the polycarbonate resin composition having excellent matte properties and solar reflectivity according to claim 1 or 2, wherein the solar reflectance measured in accordance with JIS K5675-2011 is 12% or more, and the gloss measured in accordance with JIS K5675-2011 is 50% or less.

Citation Information

Patent Citations

  • Granular polymer composition

    JP1988137911A

  • Molded product removed with surface luster

    JP1991058840A

  • Heat ray reflective film and its production

    JP1994144874A

  • Heat ray shielding plate

    JP1999013987A

  • Window glass

    JP2010064295A